# sin(2x)cos(x)-cos(2x)sin(x)=0

## Simple and best practice solution for sin(2x)cos(x)-cos(2x)sin(x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for sin(2x)cos(x)-cos(2x)sin(x)=0 equation:

Simplifying
sin(2x) * cos(x) + -1cos(2x) * sin(x) = 0
Remove parenthesis around (2x)
ins * 2x * cos(x) + -1cos(2x) * sin(x) = 0
Reorder the terms for easier multiplication:
2ins * x * cos * x + -1cos(2x) * sin(x) = 0
Multiply ins * x
2insx * cos * x + -1cos(2x) * sin(x) = 0
Multiply insx * cos
2cinos2x * x + -1cos(2x) * sin(x) = 0
Multiply cinos2x * x
2cinos2x2 + -1cos(2x) * sin(x) = 0
Remove parenthesis around (2x)
2cinos2x2 + -1cos * 2x * sin(x) = 0
Reorder the terms for easier multiplication:
2cinos2x2 + -1 * 2cos * x * ins * x = 0
Multiply -1 * 2
2cinos2x2 + -2cos * x * ins * x = 0
Multiply cos * x
2cinos2x2 + -2cosx * ins * x = 0
Multiply cosx * ins
2cinos2x2 + -2cinos2x * x = 0
Multiply cinos2x * x
2cinos2x2 + -2cinos2x2 = 0
Combine like terms: 2cinos2x2 + -2cinos2x2 = 0
0 = 0
Solving
0 = 0
Couldn't find a variable to solve for.
This equation is an identity, all real numbers are solutions.`